Марковские модели эргатических систем с защитой - Игнатенко, Д. В.; Наумейко, И. В.; Сова, А. В. (ХНУРЭ, 2018)
The model of Human-Machine-Environment (HME) system which reduces the price of detrimental factor recovering is worked out. Subject of research: A Markov model of HME with protective subsystem. It changes discrete states continuously at random time. The considered model of a discrete dynamical system describes a situation, where the main subsystem "produces" harmful factor, and the second subsystem - defense - is trying to reduce it.
Keywords: Марковская модель; эргатическая система